Selective Retention of an Inactive Allele of the DKK2 Tumor Suppressor Gene in Hepatocellular Carcinoma. - Yung-Feng Lin; Ling-Hui Li; Chih-Hung Lin; Mei-Hua Tsou; Ming-Tai Kiffer Chuang; Keh-Ming Wu; Tsai-Lien Liao; Jian-Chiuan Li; Wei-Jie Wang; Angela Tomita; Beverly Tomita; Shiu-Feng Huang; et al. (PLoS Genetics)
In an effort to identify the functional alleles associated with hepatocellular carcinoma (HCC), we investigated 152 genes found in the 4q21-25 region that exhibited loss of heterozygosity (LOH). A total of 2,293 pairs of primers were designed for 1,449 exonic and upstream promoter regions to amplify and sequence 76.8-114 Mb on human chromosome 4. Based on the results from analyzing 12 HCC patients and 12 healthy human controls, we discovered 1,574 sequence variations. Among the 99 variants associated with HCC (p < 0.05), four are from the Dickkopf 2 (DKK2) gene: three in the promoter region (g.-967A>T, g.-923C>A, and g.-441T>G) and one in the 5'UTR (c.550T>C). To verify the results, we expanded the subject cohort to 47 HCC cases and 88 healthy controls for conducting haplotype analysis. Eight haplotypes were detected in the non-tumor liver tissue samples, but one major haplotype (TAGC) was found in the tumor tissue samples. Using a reporter assay, this HCC-associated allele registered the lowest level of promoter activity among all the tested haplotype sequences. Retention of this allele in LOH was associated with reduced DKK2 transcription in the HCC tumor tissues. In HuH-7 cells, DKK2 functioned in the Wnt/β-catenin signaling pathway, as an antagonist of Wnt3a, in a dose-dependent manner that inhibited Wnt3a-induced cell proliferation. Taken together, the genotyping and functional findings are consistent with the hypothesis that DKK2 is a tumor suppressor; by selectively retaining a transcriptionally inactive DKK2 allele, the reduction of DKK2 function results in unchecked Wnt/β-catenin signaling, contributing to HCC oncogenesis. Thus our study reveals a new mechanism through which a tumor suppressor gene in a LOH region loses its function by allelic selection.